Evaluasi kemampuan ekstrak batang jahe (zingiber officinale roscoe) sebagai larvasida alami terhadap nyamuk aedes aegypti - Rahmayanti Rahmayanti; Siti Hadijah; Safridha Kemala Putri (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: The spread of mosquitoes can be stopped by one of the ways, namely by eradicating mosquito nests and killing mosquito larvae. Ginger plants, especially ginger stems, are one of the local plants that can be used as natural larvicide. The active substances in ginger stems are essential oils, saponins, alkaloids and proteolytic enzymes.Objectives: To determine the ability of ginger stem extract (Zingiber officinale roscoe) as a natural larvicide against Aedes aegypti mosquitoes.Methods: This study is an experimental research conducted in the laboratory, carried out in July 2024. The sample used in this study was Aedes aegypti instar III mosquito larvae. The treatment involved five effective concentrations of ginger stem extract, namely 0,2%, 0,4%, 0,6%, 0,8%, and 1%, as well as a negative control group using distilled water. Each treatment group consisted of 25 larvae. Data analysis was carried out using the Aedes aegypti larval mortality percentage formula and Probit analysis to determine the LC50 value.Results: The results of the study showed that the average mortality of larvae at a concentration of 0,2% reached 2 (8%), at a concentration of 0,4% as many as 3 (12%), at a concentration of 0,6% recorded 4 (16%), at a concentration of 0,8% reached 6 (24%), and at a concentration of 1% recorded 11 (44%). In the negative control, no deaths were seen, and the results of the probit test showed an LC50 value of 1,132%, with a lower limit of 0,983% and an upper limit of 1,404%.Conclusion: Ginger stem extract (Zingiber officinale roscoe) is effective as a natural larvicide against Aedes aegypti mosquitoes with a maximum consumption of 1% achieving 44% mortality and an LC50 value of 1,13%.